Does neonatal brain ischemia induce schizophrenia-like behavior in young adult rats? - Tejkalová, H; Kaiser, M; Klaschka, J; Stastný, F (Physiological research, 2007)
Perinatal cerebral hypoxia represents a major cause of obstetric complications and the resulting transient oxygen deficiency might belong to early risk factors for schizophrenia. The aim of this study was to evaluate possible long-term behavioral changes induced by one hour of continuous bilateral common carotid artery occlusion in 12-day-old male rats. Post-ischemic behavioral disturbances were evaluated in social (play) behavior on postnatal day 22 (PND 22), open field test (PND 35 and 50) and prepulse inhibition of the acoustic startle reflex (PND 50). Transient ischemia in neonatal rats was not significantly altered in social dyadic interactions evaluated in pre-weaning pups, but resulted in enhanced locomotor activity in pubertal rats (PND 35) and impaired prepulse inhibition of the startle reflex in post-pubertal males (PND 50). These behavioral alterations suggest that perinatal hypoxic/ischemic insults may represent a risk factor for later manifestation of specific features relevant to schizophrenia in predisposed individuals.
Keywords: akustická stimulace; úleková reakce; Animals; novorozená zvířata; Carotid Artery, Common; Female; Ligation; Rats, Wistar; Acoustic Stimulation; ženské pohlaví; Schizophrenic Psychology; pohybová aktivita; Animals, Newborn; chování zvířat; ischemie mozku; analýza krevních plynů; Male; modely nemocí na zvířatech; arteria carotis communis; ligace; Brain Ischemia; Disease Models, Animal; krysa rodu Rattus; Behavior, Animal; Motor Activity; Reflex, Startle; Blood Gas Analysis; Social Behavior; zvířata; mužské pohlaví; sociální chování; schizofrenie (psychologie); Rats; potkani Wistar